TEKNIK BUDIDAYA Chlorella sp. DALAM AIR TAWAR DI BALAI PENGEMBANGAN TEKNOLOGI PERIKANAN BUDIDAYA (BPTPB) CANGKRINGAN, YOGYAKARTA - Fatimah, Nurul; Hidayati, Sri; Tartila, Shobrina Silmi Qori; Laras, Aridian (Universitas Teuku Umar, 2023)
This study aimed to observe the culture technique of Chlorella sp. at BPTPB Cangkringan, Yogyakarta. Data were collected from direct observation by following the culture implementation and various literature studies in fresh water. From the observation result, the semi-mass scaled culture obtained the highest population density after 8-th day of culture at 2.970 x 104 cells/ml. The growth rates of Chlorella sp. in semi-mass scaled culture were 0.4298 x 104 cells/ml. The water quality of Chlorella sp. culture in semi-mass conditions was remained at 27-28oC, pH 7, and salinity 1 ppt. Nevertheless, the semi-mass scaled culture activity depends on the weather condition and good fertilizer quality to optimize the Chlorella sp. growth.